ABILITY AND IMPACT OF GOVERNMENT INVESTMENT SPENDING ON RAISING CREDITWORTHINESS INDICATORS LEVEL IN IRAQ FOR THE PERIOD (2004-2020) - Khalaf Mohamed Hamad; Abdul Razzaq Jafal Khalaf (Scholar Express Journals, 2022)
Investment spending is one of the important tools that lead to the expansion of Iraqi economic activity and thus increase productivity, which leads to an increase in exports and a decrease in imports, and thus reaching a surplus in the trade balance
Keywords: Government investment spending; creditworthiness; external debt; economic growth